PARP-Inhibitors in BRCA-Associated Pancreatic Cancer - Bhalla, Anshul; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Recent data suggests that treatingpatients with pancreatic cancer that express mutations in BRCA1, BRCA2, and PALB2 with chemotherapy which targets the DNA repair defect in these cells, such as platinum based therapies or PARPi [poly (ADP-ribose) polymerase inhibitor], may be more beneficial in these patients. Moreover, further data also indicates the promise of combining PARPi with conventional chemotherapy. Authors summarize the data related to PARPi in BRCA-associated pancreatic cancer that was presented at the annual meeting of ASCO 2014. Enrolment on a clinical trial for patients who fit these criteria should be encouraged. Image: Schematic representation of PARP and BRCA mediated DNA repair.